Reflection session in the ‘Basics of Biology Learning’ Lecture: Pre-service Biology Teacher’s Perspective in Choosing Learning Method/Model - Marisa Christina Tapilouw (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2020)
This study was done during the reflection session at the end of the ‘Basics of Biology Learning’ lecture. In the lecture, the students learned about many types of learning methods and models. The study was carried out to strengthen the learning material. The research problem is related to pre-service teaching students’ confusion about choosing a learning method/model. The objective of this study is to obtain information from pre-service biology teachers’ perspectives about choosing a learning method and model within a biology lesson. Their preferences of learning methods and models was based on their reasoning. The subjects of this study were five biology pre-service teaching students who attended the lectures for one semester. The interview method was used in this study; interviews were based on one open-ended question to allow the teachers to express their personal viewpoint. The result showed that, as biology teachers, their preferred methods were the discussion method, scientifical model (inquiry and problem based learning) and cooperative learning. Based on the results, the teachers’ learning method and model preferences depended on their reasoning and the way the lecturer presented the material during the lecture. At the end of the lecture, as a conclusion, there was a reflection session to find out more about students’ perspective regarding their learning during the session.